2012
DOI: 10.1038/ngeo1387
|View full text |Cite
|
Sign up to set email alerts
|

Recent extensional tectonics on the Moon revealed by the Lunar Reconnaissance Orbiter Camera

Abstract: Large-scale expressions of lunar tectonics-contractional wrinkle ridges and extensional rilles or graben-are directly related to stresses induced by mare basalt-filled basins 1,2 . Basin-related extensional tectonic activity ceased about 3.6 Gyr ago, whereas contractional tectonics continued until about 1.2 Gyr ago 2 . In the lunar highlands, relatively young contractional lobate scarps, less than 1 Gyr in age, were first identified in Apollo-era photographs 3 . However, no evidence of extensional landforms wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 23 publications
(39 reference statements)
3
62
0
8
Order By: Relevance
“…The small-scale lineations represented by E-W grooves and pit crater chains could have a tectonic origin related to the Saturnalia Fossae system. Similar, although smaller, lineations associated with extensional tectonics have been observed on the Moon (e.g., Watters et al, 2012).…”
Section: Geologic Mapmentioning
confidence: 50%
“…The small-scale lineations represented by E-W grooves and pit crater chains could have a tectonic origin related to the Saturnalia Fossae system. Similar, although smaller, lineations associated with extensional tectonics have been observed on the Moon (e.g., Watters et al, 2012).…”
Section: Geologic Mapmentioning
confidence: 50%
“…The formation of the young graben near Promontorium Laplace may have been allowed by the relative uplift of the region by the thermal subsidence of the surrounding regions. The hot interior of the terrain may have mitigated the horizontal compression by the global cooling, as was suggested for the fresh grabens by Watters et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Howard and Muehlberger (1973) found fissures along the crest of a mare ridge in Serenitatis. Watters et al (2012) and French et al (2015) found the swarms of fissures and grabens in the areas where the surface layers have been subjected to buckling along the crests of ridge-like rises. French et al (2015) also reported globally distributed small-scale grabens that are not associated with compressional features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations